2016
DOI: 10.3399/bjgp16x683437
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognised bipolar disorder among UK primary care patients prescribed antidepressants: an observational study

Abstract: Among people aged 16-40 years prescribed antidepressants in primary care for depression or anxiety, there is a substantial proportion with unrecognised bipolar disorder. When seeing patients with depression or anxiety disorder, particularly when they are young or not doing well, clinicians should review the life history for evidence of unrecognised bipolar disorder. Some clinicians might find the MDQ to be a useful supplement to non-standardised questioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
2
19
1
Order By: Relevance
“…This rate is higher than in previous literature from the UK. In samples of primary care patients, Hughes et al 10 found a prevalence of 7.3% whereas Smith et al found a prevalence of 9.6%. Both studies assessed patients with depressive disorder who had been prescribed antidepressant medication.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This rate is higher than in previous literature from the UK. In samples of primary care patients, Hughes et al 10 found a prevalence of 7.3% whereas Smith et al found a prevalence of 9.6%. Both studies assessed patients with depressive disorder who had been prescribed antidepressant medication.…”
Section: Discussionmentioning
confidence: 97%
“…Recent screening studies of bipolar disorder in UK primary care have identified that between 7 and 10% of individuals with depression may have undiagnosed bipolar disorder, usually bipolar disorder type II. 9 , 10 It is also the case that individuals with difficult to treat depression and those with poor response to antidepressants are more likely to have unrecognised bipolar disorder. 11 …”
mentioning
confidence: 99%
“…However, this approach would require a substantially larger training set size and limit the amount of user data available for future exploratory analyses. Introducing such digital instruments into primary healthcare, where resources are scarce and where symptoms of BD often remain undiagnosed 42 , has the potential to lessen the burden experienced by both patients and medical professionals, and therefore reduce the overall load on the healthcare system. In particular, such an approach could constitute a cost- and time-effective alternative to conventional, interview-based methods, while allowing for a more comprehensive symptom assessment and identification of patients who require specialty care services early in the mental health triage process.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommended 'When seeing patients with depression or anxiety disorder, particularly when they are young or not doing well, clinicians should review the life history for evidence of unrecognised bipolar disorder.' 3 Therefore if the patient has had periods of inappropriately elevated mood, overactivity, or disinhibited behaviour which have lasted for 4 days or more, consider referral for a specialist mental health assessment.…”
Section: Detecting Bipolar Disordermentioning
confidence: 99%